2011
DOI: 10.1007/s12010-011-9329-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Thermophilic Fungus Rhizomucor pusillus NRRL 28626 in Biotransformation of Antihelmintic Drug Albendazole

Abstract: In the present investigation, thermophilic fungus Rhizomucor pusillus was used to study biotransformation of antihelmintic drug albendazole to produce its active metabolite, albendazole sulfoxide and novel metabolites of commercial interest. A two-stage fermentation procedure was followed for biotransformation of albendazole. The transformation was identified and structures were confirmed by high-performance liquid chromatography and liquid chromatography-tandem mass spectrometry analysis. Four metabolites alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 21 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…These results again confirmed that heat-resistant filamentous fungi contribute to the degradation of macromolecular starch in S-NXDQ. Inversely, some fungal genera, such as Rhizomucor , could secrete lactic acid and contribute to the acidity formation [ 29 ]. This could be one of the reasons that a higher acidity was detected in MYP_N.…”
Section: Discussionmentioning
confidence: 99%
“…These results again confirmed that heat-resistant filamentous fungi contribute to the degradation of macromolecular starch in S-NXDQ. Inversely, some fungal genera, such as Rhizomucor , could secrete lactic acid and contribute to the acidity formation [ 29 ]. This could be one of the reasons that a higher acidity was detected in MYP_N.…”
Section: Discussionmentioning
confidence: 99%